Regio- and diastereoselective synthesis of (E)-3-(2-aminochromen-4-yl)-6-aryl-substituted fulvenes - Koz, Gamze; Şahin, O.; Coşkun, N. (Verlag der Zeitschrift fur Naturforschung, 2016)
A practical base-catalyzed route was developed for the regio- and diastereoselective synthesis of (E)-3-aminochromene-6-aryl-disubstituted fulvenes in high yields up to 94% starting with the Michael addition of cyclopentadiene to 2-iminochromenes in the key step. © 2016, Verlag der Zeitschrift fur Naturforschung. All rights reserved.
Keywords: Aminochromene; Base catalysis; Cyclopentadiene; Fulvene; Michael addition